AN IN VITRO ANTAGONISTIC EFFECT OF Trichoderma spp. AGAINST Fusarium oxysporum f.sp. lycopersici (FUDMA JOURNAL OF SCIENCES, 2023)
The experiment was conducted in the Department of Plant Pathology, Sam Higginbottom University of Agriculture, Technology and Sciences, Allahabad, India. Diseased tomato stems and roots showing symptoms of Fusarium wilt were collected from the Research and Training plots of the Department. The pathogen isolated was identified as Fusarium oxysporum f.sp. lycopersici. Nine native Trichoderma strains were isolated from healthy tomato rhizosphere soils from three different locations of Allahabad; viz Naini, Sangam and Prayagraj. Six isolates were found to be strains of Trichoderma harzianum (SP-4, Th-6, Th-3, Th-5, RTM-16 and EPI-5) while the three were of Trichoderma viride (SP-1, KI-9, SP-3). They were examined in the laboratory for the control of pathogen Fusarium oxysporum. The results revealed that all Trichoderma spp. isolates were found to effectively inhibit the mycelial growth of the pathogen compared to control. However, significant differences between the species and strains were found (P
Keywords: Antagonistic, Fusarium, Tomato and Trichoderma